Sugammadex by ideal body weight versus 20% and 40% corrected weight in bariatric surgery - double-blind randomized clinical trial - Duarte,Nádia Maria da Conceição (2018)
Abstract Background and objectives: The weight parameters for use of sugammadex in morbidly obese patients still need to be defined. Methods: A prospective clinical trial was conducted with sixty participants with body mass index ≥ 40 kg.m-2 during bariatric surgery, randomized into three groups: ideal weight (IW), 20% corrected body weight (CW20) and 40% corrected body weight (CW40). All patients received total intravenous anesthesia. Rocuronium was administered at dose of 0.6 mg.kg-1 of Ideal weight for tracheal intubation, followed by infusion of 0.3-0.6 mg.kg-1.h-1. Train of four (TOF) was used to monitor depth of blockade. After spontaneous recovery TOF-count 2 at the end of surgery, 2 mg.kg-1 of sugammadex was administered. Primary outcome was neuromuscular blockade reversal time to TOF ≥ 0.9. Secondary outcome was the occurrence of postoperative residual curarization in post-anesthesia recovery room, searching the patient's ability to pass from the surgical bed to the transport, adequacy of oxygenation, respiratory pattern, ability to swallow saliva and clarity of vision. Results: Groups were homogenous in gender, age, total body weight, ideal body weight, body mass index, type and time of surgery. The reversal times (s) were (mean ± standard deviation) 225.2 ± 81.2, 173.9 ± 86.8 and 174.1 ± 74.9 respectively, in the IW, CW20 and CW40 groups (p = 0.087). Conclusions: No differences were observed between groups with neuromuscular blockade reversal time and frequency of postoperative residual curarization. We concluded that ideal body weight can be used to calculate sugammadex dose to reverse moderate neuromuscular blockade in morbidly obese patients.